Introduction - Baldwin, Clive (Narrative Works)

(untitled) (The University of New Brunswick, 2016)
The editors of Narrative Works solicited the five papers of this special issue from major writers and thinkers in the field of narrative. The authors were asked to speak to the importance and role of narrative in their work and discipline, in the hope of somewhat clarifying what it is that narrative is and does, and perhaps providing a basis for seeing links between disciplines and approaches that might further narrative scholarship. In this introduction, I focus on how the five contributions have prompted me to think, or think again, about how I go about my own work in narrative. Approaching the literature in this way puts me in mind of Valéry’s stance on reading the work of others: “But I am not much of a reader, since what I look for in a work is what will enable or impede an aspect of my own activity” (cited in Bayard, 2007, pp. 15–16). Yet for me, if not Valéry, this is not to devalue the work of others, but to recognize that such works provide vital nourishment for my own. In what follows, I hope to encourage others to explore how they, too, might find nourishment in these pages.